fMRI neurofeedback in the motor system elicits bidirectional changes in activity and in white matter structure in the adult human brain - Sampaio-Baptista, C; Johansen-Berg, H; Neyedli, HF; Sanders, Z-B; Diosi, K; Havard, D; Huang, Y; Andersson, JLR; Lühr, M; Goebel, R (Cell Press, 2021)
White matter (WM) plasticity supports skill learning and memory. Up- and downregulation of brain activity in animal models lead to WM alterations. But can bidirectional brain-activity manipulation change WM structure in the adult human brain? We employ fMRI neurofeedback to endogenously and directionally modulate activity in the sensorimotor cortices. Diffusion tensor imaging is acquired before and after two separate conditions, involving regulating sensorimotor activity either up or down using real or sham neurofeedback (n = 20 participants × 4 scans). We report rapid opposing changes in corpus callosum microstructure that depend on the direction of activity modulation. Our findings show that fMRI neurofeedback can be used to endogenously and directionally alter not only brain-activity patterns but also WM pathways connecting the targeted brain areas. The level of associated brain activity in connected areas is therefore a possible mediator of previously described learning-related changes in WM.